SOSIALISASI JASP: PELATIHAN ANALISIS DATA STATISTIK BAGI AKADEMISI MAKASAR (Jurnal AbdiMas Nusa Mandiri, 2026)
Limited access to licensed statistical software is one of the obstacles in strengthening data analysis competencies at the Makassar Ujung Pandang Education Foundation (YPUP) College of Teacher Training and Education (STKIP). The introduction of free and open-source statistical software such as Jeffreys's Amazing Statistics Program (JASP) has encouraged the implementation of this service activity. The activity aims to increase literacy and readiness to use legal and easily accessible alternative statistical software. The workshop was held online on July 11–12, 2025 with a participatory training approach that included presentation of educational research design, demonstration of the use of JASP, as well as descriptive, parametric, and non-parametric statistical analysis practices. There were 37 participants including lecturers and students, with 33 participants filling out the evaluation instruments. The evaluation was carried out descriptively through a self-assessment questionnaire to measure the level of understanding of participants after the training. The results showed that 32.73% of participants strongly agreed and 67.27% agreed that they had understood the use of JASP. These findings indicate an increase in initial literacy and readiness for the adoption of open-source-based statistical software. Although the objective measurement of the improvement of analytical skills through pre-test and post-test has not been carried out, this activity opens opportunities for the integration of JASP in learning and research and becomes the basis for planning further assistance as a form of program sustainability.
Keywords: data analysis; Jeffreys's Amazing Statistics Program (JASP); workshop